ANALISIS PENGENDALIAN MUTU DENGAN MENGGUNAKAN STATISTICAL QUALITY CONTROL (SQC) PADA PT.PRATAMA ABADI INDUSTRI (JX) SUKABUMI - Andespa, Ira (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
The theme and main issues in this research are the ineffectiveness of the implementation of quality control applied to the company so that the high level of product defects or reject that exceeds the specified tolerance limit of 2.5%. Then analyzed what are the factors causing the occurrence of defective products using statistical aids or statistical quality control (SQC) to minimize the occurrence of defective products at PT.Pratama Abadi Industri (JX) Sukabumi. The research method used by the author in this study uses quantitative descriptive method where the analysis technique used by the author is using statistical analysis techniques with 7 statistical tools or seven tools (check sheet, histogram, pareto diagram, scatter diagram, control chart, stratification, and causal diagram). From the results of research using the 7 statistical quality control tools that have been analyzed using a control map or P-Chart, it can be seen that the cause of irregularities that occur in PT. untidy stitches (22.19%), torn rubber (16.67%), fissures / boanding (15.68%), Gross (15.89%), faded logos (14.05%), and accessories are swapped ( 15.53%). As a result of the occurrence of irregularities, the company still produces products with quality that are included in the category of defects B-Grade ¬ and also C-Grade.